Outcomes of clinical diabetes research at the Teaching Hospital and Faculty of Medicine, Palacký University Olomouc (1971–2014) - Chlup, R. (Fundamental and Experimental Biology, 2015)
This paper summarizes results of clinical studies in the period of years 1971–2014 as follows: (1) In persons with type 1 diabetes, effectiveness of conventional therapy with multiple doses of shortacting insulin (MDI) or continuous sucutaneous insulin infusion (CSII) was demonstrated. Dynamic training was shown to enhance insulin sensitivity and plasma HDL cholesterol, and to improve neuropathy, memory and attention. Influence of alcohol and effects of insulin on postprandial alcohol concentrations revealed similar consequences; model experiments were suggested when answering forensic questions. (2) In persons with type 2 diabetes, advantage of complementary therapy with prandial rapid acting insulin was demonstrated. In MDI-persistent hyperglycaemia, insulin pump was shown to reduce HbA1c, to diminish daily insulin dose and to improve quality of life. Benefits of incretin preparations were described. Effects of losartan on renal and cardiovascular outcomes in diabetic nephropathy were documented. (3) Perinatal mortality of newborns of mothers with diabetes decreased due to thorough diabetes and obstetric care. (4) Manual Device for Insulin injections (MADI-pen) was developed and introduced into daily routine. Its accuracy, pharmacological and microbial safety were proved. (5) «Programmed Treatment of persons with diabetes» comprising the principels of Therapeutic Patients Education of the WHO was introduced. (6) Glycaemic Index of foods was calculated using a new method with continuous glucose monitoring. (7) Intensive selfmonitoring. The accuracy and precision of various glucometers were explored. Tenpoint ambulatory glycaemic profile and continuous glucose monitoring system (CGMS) was introduced to practice. In persons on insulin pumps CGMS re-sulted in reduction of HBA1c.